Penggunaan Bahan Baku tidak Berkelanjutan dalam Rantai Pasok Global Nestle dan Dampaknya terhadap Kerusakan Lingkungan - Jessyca Natasya Kaunang (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
This study examines the gap between Nestlé’s sustainability commitments and the reality of ecological damage caused by the use of unsustainable raw materials in its global supply chain. Using a descriptive qualitative approach based on literature reviews and case study analysis, this study evaluates various data sources, ranging from scientific journals and corporate reports to documentation from independent organizations such as Greenpeace and the Rainforest Action Network. Findings indicate that Nestlé’s procurement of key commodities such as palm oil, cocoa, soy, dairy products, and singleuse plastics significantly contributes to deforestation, systemic plastic pollution, water extraction in vulnerable regions, and greenhouse gas emissions exceeding 87.5 million tons of CO₂e per year. In Indonesia, these highrisk areas are evident in palm oil sourcing in Sumatra and Kalimantan and cocoa sourcing in Sulawesi. Theoretically, this study argues that Nestlé’s sustainability governance exhibits a pattern of strategic decoupling, where public reporting on progress in primary supply chains is deliberately used to mask ongoing environmental damage within their hidden supply networks. Thus, this article makes a critical contribution by integrating supply chain management theory, environmental accountability, and the governance of multinational corporations.